EFFICACY OF FUNCTIONAL ENDOSCOPIC SINUS SURGERY IN RECURRENT NASAL POLYPOSIS - Sohail Aslam; Mohammad Ali; Attique Ahmed; Adnan Asghar; Mohammad Adnan Manzar (Pakistan Armed Forces Medical Journal, 2013)
Objective: To analyze the efficacy of FESS in patients with recurrent nasal polyposis in terms of relief of nasal obstruction, improvement in sense of smell and to assess recurrence of disease. Study Design: Descriptive case series. Materials and Method: All patients who underwent FESS (Functional endoscopic sinus surgery) for recurrent nasal polyposis from June 2008 to June 2010 with an average follow up of 06 month were included. Clinical symptoms including nasal obstruction and olfactory disturbance were evaluated using VAS system pre and postoperatively. Preoperatively computed tomography scan was done in all cases to assess extent of disease and surgical anatomy. Results: Following FESS 96% of total patients demonstrated statistically significant improvement in relieving nasal obstruction after 6 months follow up, however improvement in sense of smell was seen in 44% of patients. Recurrence was seen in only 3 (6%) cases at 3rd and 6th month follow up. Conclusion: Functional endoscopy sinus surgery of recurrent nasal polyposis is an effective method of surgery with significant improvement of symptom of nasal obstruction and olfaction with minimal recurrence at 6 month in our centre. Our results were compatible with results attained internationally.